Comparing the Effects of Isoflurane and Alpha Chloralose upon Mouse Physiology - Low, Lucie A.; Bauer, Lucy C.; Klaunberg, Brenda A. (PLOS ONE, 2016)
Functional magnetic resonance imaging of mice requires that the physiology of the mouse (body temperature, respiration and heart rates, blood pH level) be maintained in order to prevent changes affecting the outcomes of functional scanning, namely blood oxygenation level dependent (BOLD) measures and cerebral blood flow (CBF). The anesthetic used to sedate mice for scanning can have major effects on physiology. While alpha chloralose has been commonly used for functional imaging of rats, its effects on physiology are not well characterized in the literature for any species. In this study, we anesthetized or sedated mice with isoflurane or alpha chloralose for up to two hours, and monitored physiological parameters and arterial blood gasses. We found that, when normal body temperature is maintained, breathing rates for both drugs decrease over the course of two hours. In addition, alpha chloralose causes a substantial drop in heart rate and blood pH with severe hypercapnia (elevated blood CO2) that is not seen in isoflurane-treated animals. We suggest that alpha chloralose does not maintain normal mouse physiology adequately for functional brain imaging outcome measures.